A Comparative Study of Technical Efficiency of Rice Production in Irrigated and Rainfed Environment of Uttrakhand - Rani, Rekha; Singh, H. N. (Indian Journal of Hill Farming, 2016)
Agriculture has a key position in India’s economy in respect of employment generation and contribution to the national income and international trade. Keeping its importance in view it becomes important to study how improvements can be made in the productivity of this sector. In this paper an attempt has been made to estimate farm level technical efficiency of rice production in two distinct rice growing environments viz. rainfed and irrigated environment of uttarakhand state. Technical efficiency is the effectiveness with which a given set of inputs is used to produce an output. The primary data was collected from 60 farmers, 30 each from rainfed and irrigated environment of the hill district during 2011-12 year. To determine technical efficiency of the farmers, frontier production function was estimated by using Corrected Ordinary Least Square (COLS) technique. The calculated technical efficiency of the farmers in rainfed environment varied between 68 to 89 per cent with a mean of 79 per cent whereas in irrigated environment technical efficiency of the farmers varied between 86 to 99 per cent with a mean of 94 per cent. It indicates that about 21 per cent less than maximum possible output is being obtained in rainfed environment whereas in irrigated it was 6 per cent less than the maximum possible output. The study suggest that the policy measures like effective and flexible agricultural extension network should be adopted in different environments as per their suitability so that the resources can be utilized efficiently and maximum output can be achieved from the available inputs.